Prevalence and characteristics of foodborne pathogens from slaughtered pig carcasses in Korea - Hong, Serim; Kang, Hye Jeong; Lee, Hye-Young; Jung, Hye-Ri; Moon, Jin-San; Yoon, Soon-Seek; Kim, Ha-Young; Lee, Young Ju (Frontiers in Veterinary Science, 2023)
The introduction of bacteria into slaughterhouses can lead to microbial contamination in carcasses during slaughter, and the initial level of bacteria in carcasses is important because it directly affects spoilage and the shelf life. This study was conducted to investigate the microbiological quality, and the prevalence of foodborne pathogens in 200 carcasses from 20 pig slaughterhouses across Korea. Distribution of microbial counts were significantly higher for aerobic bacteria at 3.01–4.00 log10 CFU/cm2 (42.0%) and 2.01–3.00 log10 CFU/cm2 (28.5%), whereas most of Escherichia coli showed the counts under 1.00 log10 CFU/cm2 (87.0%) (P<0.05). The most common pathogen isolated from 200 carcasses was Staphylococcus aureus (11.5%), followed by Yersinia enterocolitica (7.0%). In total, 17 S. aureus isolates from four slaughterhouses were divided into six pulsotypes and seven spa types, and showed the same or different types depending on the slaughterhouses. Interestingly, isolates from two slaughterhouses carried only LukED associated with the promotion of bacterial virulence, whereas, isolates from two other slaughterhouses carried one or more toxin genes associated with enterotoxins including sen. In total, 14 Y. enterocolitica isolates from six slaughterhouses were divided into nine pulsotypes, 13 isolates belonging to biotype 1A or 2 carried only ystB, whereas one isolate belonging to bio-serotype 4/O:3 carried both ail and ystA. This is the first study to investigate microbial quality and the prevalence of foodborne pathogens in carcasses from slaughterhouses nationally, and the findings support the need for ongoing slaughterhouse monitoring to improve the microbiological safety of pig carcasses.